Discovery, SAR, and putative mode of action of N‐benzyl‐2‐methoxybenzamides as potential bleaching herbicides. Issue 6 (17th February 2021) - Zhang, Huixia; Wang, Jinbo; Ji, Zhenmeng; Sun, Xinlin; Tian, Qizhen; Wei, Shaopeng; Ji, Zhiqin
Abstract: BACKGROUND: Herbicides acting on biosynthesis of plant pigments have contributed greatly to weed control in recent years. In our previous studies, 2‐methoxybenzamides were discovered as a novel type of lead compound for the development of bleaching herbicides. RESULTS: A total of 67 benzamide analogues were synthesized and evaluated for herbicidal activity. The structure–activity relationship (SAR) revealed that a methoxyl substitution at the 2‐position of the benzoyl moiety is essential for the herbicidal activity of benzamide derivatives, and introduction of small substituents at the meta ‐ or para ‐position of the benzylamine moiety is also beneficial. Compounds 4, 43 and 44 showed 100% inhibition against Abutilon theophrasti and Amaranthus retroflexus at an application rate of 150 g a.i. ha −1 . CONCLUSION: The relationship between the structure and herbicidal activity of 2‐methoxybenzamides was discussed intensively. Compounds 4, 43 and 44 may serve as novel candidates with a bleaching effect. © 2021 Society of Chemical Industry Abstract : The herbicidal activity of N ‐benzyl‐2‐methoxybenzamide was discovered using a random screening procedure. Sixty‐seven N ‐benzyl‐2‐methoxybenzamides were synthesized and evaluated for herbicidal activity. Their structure–activity relationship was discussed thoroughly.